Норвежката литература в България през последните две години (2020/2021): теми, мотиви, преводни особености - Тетимова, Евгения (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2021)
The publication provides a brief overview of the overall reception of Norwegian literature in Bulgaria from the Liberation to the present day. It focuses mainly on three books translated from Norwegian in the last two years (2020/2021) - Against nature by Thomas Espedal, The Undead by Linn Ullmann and Trilogy by Jon Fosse. The aim is to analyze the main themes and motives in these translated works, to highlight their stylistic characteristics and their transmission in translation into Bulgarian. Based on the comparison between translated and original works examples of difficulties, challenges and good translation solutions in translating certain linguistic and stylistic features from Norwegian into Bulgarian are given.